2015
DOI: 10.4137/bmi.s27625
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neutrophil Gelatinase-Associated Lipocalin to Monitor Lupus Nephritis Disease Activity

Abstract: BACKGROUNDThis study was conducted to determine whether there is an association between urinary neutrophil gelatinase-associated lipocalin (uNGAL) and urinary transforming growth factor-β1 (uTGF-β1) with lupus nephritis (LN) disease activity.METHODSUrine samples from 18 LN patients were collected every month for six months then examined for uNGAL, uTGF-β1, and renal domain Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score.RESULTSThe uNGAL levels were significantly different between active and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies had heterogenous results regarding this issue. Some studies showed a significant correlation between uNGAL with renal SLEDAI (rSLEDAI) and concluded its valuable use as a predictor of renal involvement [ 16 , 33 , 34 ]. However, other concluded that uNGAL is a strong predictor of rSLEDAI score but was not a strong predictor for total SLEDAI score [ 20 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had heterogenous results regarding this issue. Some studies showed a significant correlation between uNGAL with renal SLEDAI (rSLEDAI) and concluded its valuable use as a predictor of renal involvement [ 16 , 33 , 34 ]. However, other concluded that uNGAL is a strong predictor of rSLEDAI score but was not a strong predictor for total SLEDAI score [ 20 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In juvenile SLE patients, both urine monocyte chemoattractant protein-1 (uMCP1) and serum C3 can indicate renal involvement, while both uMCP1 and uNGAL can predict subsequent renal disease activity changes [ 38 ]. Other studies showed that uNGAL can differentiate between active and inactive LN [ 34 , 39 ]. The same finding was proven as regard uKIM-1 as predictors for changes in lupus nephritis activity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%